Evaluation of irrigation levels and plant geometry for drip irrigation in groundnut (Arachis hypogaea L.): EVALUATION OF IRRIGATION LEVELS AND PLANT GEOMETRY FOR DRIP IRRIGATION IN GROUNDNUT - C HARISUDAN; K SUBRAHMANIYAN (Journal of Oilseeds Research, 2020)
Field experiments were conducted for two consecutive years during kharif 2013 and 2014 to evaluate the irrigation levels and plant geometry for drip irrigation in groundnut. The experiment was laid out in split plot design with different irrigation levels in main plots viz., I1 - 100% of daily evaporation rate (Td) by drip every alternate day, I2 - 80% of daily evaporation rate (Td) by drip every alternate day, I3 - 60% of daily evaporation rate (Td) by drip every alternate day, I4 - Border strip irrigation at 1.0 IW/CPE ratio irrigation water depth (5cm). In sub plots four plant geometry levels were imposed viz., G1 - Conventional sowing (row to row : 30 cm ) with one lateral to each row, G2 - One lateral between two rows, G3 - Paired - rows (15/30 cm apart) with one median lateral to each pair, G4 - One lateral between two pairs. All the treatments were replicated three times. Among the different irrigation levels, irrigating the groundnut at 100% average daily evaporation rate (Td) by drip at alternate days had significant effect on groundnut growth and yield parameters and registered higher pod yield of 2250 kg/ha. Among the different plant geometry one lateral between two pairs significantly influenced the growth and yield parameters and recorded higher pod yield of 2205 kg/ha.